Pengaruh Disiplin Belajar dan Lingkungan Keluarga Terhadap Hasil Belajar Siswa di SMA Sunan Giri Menganti - Wibowo, Adila Putra (Universitas Negeri Surabaya, 2024)
The aim of this research is to analyze and describe the influence of learning discipline and family environment on the learning outcomes of class X students at SMA Sunan Giri Menganti Gresik partially and simultaneously. In this research, researchers used quantitative research with an associative approach. Based on calculations using the Slovin formula, the samples used in this research were 82 students of Sunan Giri Menganti Gresik. Data analysis using multiple linear regression analysis. The results of the research show that partially and simultaneously the learning discipline variable and the family environment variable have a positive and significant effect on the learning outcome variables for class X at SMA Sunan Giri Menganti Gresik.